Dictionary of cults, sects, religions, and the occult - Mather, George A; Nichols, Larry A (Grand Rapids, Mich. : Zondervan Pub. House, 1993)
The Dictionary of Cults, Sects, Religions and the Occult is probably the most significant reference book on the subject to be published in recent decades. In addition to traditional, well-known groups such as Jehovah's Witnesses, Mormons, Islam, and Baha'i, the Dictionary of Cults, Sects, Religions and the Occult deals with groups that are not yet well-known but are making strong inroads in North America, such as Santeria, Rastafarians, Haitian Voodoo, white supremacy groups, and Satanism. The authors evaluate the beliefs and practices of each group from the perspective of the Bible and the historic creeds of the Christian church. Numerous short articles about people, places, and concepts provide brief definitions and descriptions. These articles are cross-referenced to the major in-depth articles that deal with the history, beliefs, and demography of each cult, sect, or religion
The book contains many illustrations and charts and includes an up-to-date bibliography for each of the groups and movements
Includes bibliographical references (pages 343-384)
Keywords: Religions -- Dictionaries; Cults -- Dictionaries; Sects -- Dictionaries; Occultism -- Dictionaries